Surgical Treatment of a Case of Primary Angiosarcoma of the Right Atrium Associated with Cardiac Tamponade - Furutani, Yasuhiro; Ihara, Katsuhiko; Sakaki, Masayuki; Nomura, Fumikazu; Hamamoto, Masaki (Japanese Journal of Cardiovascular Surgery, 1999)
We report a case of angiosarcoma of the right atrium, which manifested as cardiac tamponade. A 50-year-old man was admitted to our hospital complaining of dyspnea on effort. Echocardiography and chest CT revealed massive pericardial effusion and a right atrial tumor mass. An emergency pericardiocentesis was performed to remove massive hemorrhagic fluids. Further examinations revealed primary cardiac neoplasm. Because there was no distant metastasis, the tumor in the right atrium was resected with the right atrial free wall under cardiopulmonary bypass support. The sinus node involved in the tumor was resected, necessitating pacemaker implantation. Microscopic examination of the resected tumor revealed angiosarcoma. As the resection border showed tumor tissue, postoperative radiotherapy was added. There was no evidence of recurrence or metastasis 14 months after surgery. The prognosis for angiosarcoma is very poor, and mean survival is less than 6 months. In cases with no metastases, early resection is the treatment of choice. In spite of incomplete resection, long-term survival may be possible with postoperative radiotherapy.